2020
DOI: 10.1371/journal.pone.0234385
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral mitogenome capture of the Southeast Asian banded linsang

Abstract: Utilising a reconstructed ancestral mitochondrial genome of a clade to design hybridisation capture baits can provide the opportunity for recovering mitochondrial sequences from all its descendent and even sister lineages. This approach is useful for taxa with no extant close relatives, as is often the case for rare or extinct species, and is a viable approach for the analysis of historical museum specimens. Asiatic linsangs (genus Prionodon) exemplify this situation, being rare Southeast Asian carnivores for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…2016 , 2020 ; Portik et al., 2016 , Peñalba et al., 2014 ). Additionally, variation in coverage has been observed in the capture of divergent species in previous studies ( Paijmans et al., 2020 ). Divergence between bait and target does not seem to be the sole driver of this effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2016 , 2020 ; Portik et al., 2016 , Peñalba et al., 2014 ). Additionally, variation in coverage has been observed in the capture of divergent species in previous studies ( Paijmans et al., 2020 ). Divergence between bait and target does not seem to be the sole driver of this effect.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to poor DNA preservation, previous work has shown that hybridization capture fails to recover sequences that are too divergent from the bait sequences ( Paijmans et al., 2016 , 2020 ). Since no sequences from close relatives are available, we used baits designed from members of the Elephantidae as well as the American mastodon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the same array, mitochondrial genomes for five Caprinae species were present for enrichment of samples from a different project. Prior to capture, libraries were pooled in equimolar amounts according to their mitochondrial endogenous content as determined via shotgun sequencing (Supplementary Table S3 and S4 ) 43 . Due to its already high endogenous content, the Stockholm sample was not captured.…”
Section: Methodsmentioning
confidence: 99%
“…A potential drawback of the evenness-of-coverage metric exists for cases when cross-species hybridisation enrichment was applied in the laboratory to enrich for a particular genetic region (e.g., mitogenome, exome). It has been shown that cross-species capture—i.e., when baits from a related species are used for enrichment—can introduce strong biases for regions with the highest sequence similarity between bait and target [ 74 , 75 ]. We utilised hybridization capture with dhole bait DNA, which means that the four samples that were post-hoc identified as wolf were captured with a cross-species capture approach.…”
Section: Discussionmentioning
confidence: 99%